Severity Tomographic Score (TSS) as a predictor of admission to Intensive Care Unit (ICU) in patients with COVID-19 pneumonia in San Juan de Lurigancho Lima, Peru: - Ravelo-Hernández, Jorge L. (2022)
Objective: To determine if the Tomographic Severity Score (TSS) of patients with COVID- 19 pneumonia at admission, as well as some laboratory tests or clinical features predict ICU admission in this group of patients. Material and methods: Case-control study, which included patients with a clinical diagnosis of SARS-CoV2 virus infection, performed by reverse transcriptase polymerase chain reaction (RT-PCR), reactive serological test (IgM / IgG) and/or Computed Tomography of the chest (CTT) without contrast. Two radiologists (blind evaluators) described the tomographic findings. The data were taken from electronic medical records (EHR). The most important variables for the prediction of ICU admission were analyzed: TSS, age, BMI, obesity, ferritin, D-Dimer, O2 saturation, PO2, lymphopenia, C-reactive protein, and presence of comorbidities: Diabetes Mellitus, HTN. The prediction of admission to the ICU was performed using binary logistic regression for an adjusted OR, which compared 2 analysis models with a 95% CI and a p value <0.05; as statistically significant Results: 168 participants were included. The most frequent comorbidity was arterial hypertension, followed by Type 2 diabetes, the most frequent symptoms in our series were cough, malaise, fever and respiratory distress, there were no significant differences between the groups studied (admitted to ICU and not admitted to ICU). The mean age of the patients not admitted to the ICU was 44.89 ± 10.9 years and of those admitted to the ICU 43.81 ± 11 years (p: 0.669). The mean value of the TSS Score was 14 (SD 4.44) in ICU patients vs. 7.77 (SD 4.81) in Not admitted to ICU (p <0.001), the mean D-Dimer was 0.78 (SD 2.74) in Not admitted to ICU vs. 4.72 (SD 9.72) in ICU admitted (p <0.001). In addition, the prediction for ICU admission by binary logistic regression was shown in Model 2; than the following variables: TSS (OR: 1.24) (95% CI 1.08- 1.43) (p₌ 0.002), BMI (OR: 1.19) (95% CI 1.02-1.39) (p₌ 0.022), Age (OR: 0.94) (95% CI 0.89-0.99) (p₌ 0.047) and D-Dimer (OR: 1.14) (95% CI 1.04-1.26) (p₌ 0.05), were the variables with the best predictive value. Conclusions: The TSS Score was useful in the initial diagnostic evaluation of COVID-19 pneumonia, in conjunction with markers such as D-Dimer, BMI and age that can predict a poor result in the short term. A TSS Score ≥ 8 in patients with COVID 19 pneumonia at hospital admission can be considered a predictor of admission to the ICU in the patients studied.